Emergence and spread of Neisseria gonorrhoeae isolates with decreased susceptibility to extended-spectrum Cephalosporins in Argentina, 2009 to 2013 - Gianecini, Ricardo A (2017)
Fil: Gianecini, Ricardo. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.